Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1111/j.1469-8137.2005.01560.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel form of resistance in rice to the angiosperm parasite Striga hermonthica

Abstract: Summary• The root hemiparasitic weed Striga hermonthica is a serious constraint to grain production of economically important cereals in sub-Saharan Africa. Breeding for parasite resistance in cereals is widely recognized as the most sustainable form of long-term control; however, advances have been limited owing to a lack of cereal germplasm demonstrating postattachment resistance to Striga .• Here, we identify a cultivar of rice (Nipponbare) that exhibits strong postattachment resistance to S. hermonthica ; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
218
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 151 publications
(239 citation statements)
references
References 34 publications
17
218
4
Order By: Relevance
“…Some potential resistant host plants have been reported to lack the capacity to stimulate haustorial initiation of Striga germinated seeds or to produce compounds that inhibits the formation of the haustorium, an important organ towards parasite connection to host root (Gurney et al, 2003;Rich et al, 2004;Robert, 2011). Several authors demonstrated also the establishment of mechanical barriers to protect the host root from parasite penetration and access to the host plant vascular system (Maiti et al, 1984;Gurney et al, 2006;Amusan et al, 2008;Yoshida and Shirasu, 2009). Another protecting mechanism is the recognition of the invasion as a threat and the rapid mobilization of defense response such as the hypersensitive response (HR).…”
Section: Mechanisms Of Resistancementioning
confidence: 99%
See 4 more Smart Citations
“…Some potential resistant host plants have been reported to lack the capacity to stimulate haustorial initiation of Striga germinated seeds or to produce compounds that inhibits the formation of the haustorium, an important organ towards parasite connection to host root (Gurney et al, 2003;Rich et al, 2004;Robert, 2011). Several authors demonstrated also the establishment of mechanical barriers to protect the host root from parasite penetration and access to the host plant vascular system (Maiti et al, 1984;Gurney et al, 2006;Amusan et al, 2008;Yoshida and Shirasu, 2009). Another protecting mechanism is the recognition of the invasion as a threat and the rapid mobilization of defense response such as the hypersensitive response (HR).…”
Section: Mechanisms Of Resistancementioning
confidence: 99%
“…Over the past decades, research efforts have led to the discovery of new sources of resistance to Striga in several host crops including millets and other cereals (Lane et al, 1997;Gurney et al, 2003;Karaya et al, 2012;Wilson et al, 2000Wilson et al, , 2004Gurney et al, 2006;Amusan et al, 2008;Cissoko et al, 2011). In sorghum, several cultivars and breeding lines have been reported to be resistant and/or tolerant to Striga Rodenburg et al 2006;Ejeta, 2007).…”
Section: Sources Of Resistancementioning
confidence: 99%
See 3 more Smart Citations